Heterogeneity of UK residential heat demand and its impact on the value case for heat pumps. (September 2020) - Flower, Jack; Hawker, Graeme; Bell, Keith
Abstract: This study examines the heterogeneity of UK residential heat demand and how this diversity, along with social demographic and dwelling characteristic diversity, impacts the value case for heat pumps (HPs). The marginal abatement cost (MAC) of HPs is highly sensitive to the level of heat demand and technology assumptions. Care must be taken when interpreting the results from models with a high degree of aggregation. For similar dwellings, heat demand typically becomes lower for demographic groups that have higher levels of deprivation. For similar dwellings and demographics, households using natural gas typically have double the end-use heat demands of households with electric storage heaters. Therefore, if access to heating with similar costs to that of natural gas-fired heating is gained, the direct rebound effect suggests that the heat demands of households heated with electric storage heaters could double, particularly for households that have relatively high proportions of energy expenditure. Heating technology and building efficiency support mechanisms need to simultaneously address the wider goal of decarbonisation while reducing fuel poverty, and to incorporate measures of demand diversity into future assessment of heat policy that recognises how this rebound may oppose decarbonisation efforts but enable improvements in comfort, welfare and health standards. Highlights: Heat demand typically becomes lower as deprivation increases. Households with electric storage heaters have the lowest normalised heat demands. Abatement costs are highly sensitive to heat demand and technology assumptions. There is potential for a demand rebound when implementing low carbon heating. A national heat strategy must consider within-sector diversity and broader benefits.